JURNALISME WARGA DAMPAK TSUNAMI DI ACEH (STUDI KASUS MEULABOH) - Muzakkir Muzakkir (Universitas Teuku Umar, 2018)
The article is a study in the background with observations of good citizen journalism, by preaching information that can provide positive value for the development of publications. Not a stove that always heats the situation and situation.